ANALISIS RISIKO PADA IMPLEMENTASI GOOD GOVERNMENT GOVERNANCE STUDI KASUS PADA DIREKTORAT JENDERAL KEPENDUDUKAN DAN PENCATATAN SIPIL - Rahman, Afif (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The survey was conducted by the Directorate General of Population and Resident Registration, which is involved in public services, specifically giving identity for Indonesian citizens. The survey was conducted with the aim of analyzing good governance related to risk management in the General Directorate of Population and Civil Registry. This study was carried out with the aim of analyzing risk management in the implementation of good governance in the General Directorate of Professional Civil Registry. Governments operating in the service sector and applying the principles of good governance deliver their services honestly, effectively, efficiently and free from corruption. Risk management plays an important role in minimizing the risk of impeding the provision of services in accordance with the principles of good governance. These barriers must be measured and managed in order to achieve the strategic objectives of the organization, and thus must be mitigated to minimize the opportunity and impact of the resulting risks. Based on the results of studies using SWOT analysis and risk matrices, independence of principle requires risk mitigation recommendations. The risk mitigation done to address the risks is to work with the experts and academics of the team to draft the Home Secretary Regulations or related Regulations to achieve good governance. And the Directorate General of Professional and Civil Affairs is committed to maximizing the use of call centers, which act as whistleblower systems, to illegal livy practices in employment services.